2020
DOI: 10.2147/cmar.s262450
|View full text |Cite
|
Sign up to set email alerts
|

<p>Transcriptome-Wide 5-Methylcytosine Functional Profiling of Long Non-Coding RNA in Hepatocellular Carcinoma</p>

Abstract: Background Growing evidence indicates that methylation status is associated with the pathogenesis of numerous types of cancers. Among these, hepatocellular carcinoma (HCC) is a deadly disease threatening global human health. Although 5-methylcytosine (m5C) has been identified as an important regulatory modification, its distribution in solid tumors, including HCC, remains unclear. The present study aimed to explore the distribution of m5C in HCC. Materials and Methods S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Studies have also shown that m 5 Crelated regulators play essential roles in tumor progression in HCC (11,12). Research into m 5 C modifications has also provided evidence for the epigenetic m 5 C regulation of lncRNA related to HCC tumorigenesis and progression (13). However, the specific genomic distribution of m 5 C-related genes for HCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that m 5 Crelated regulators play essential roles in tumor progression in HCC (11,12). Research into m 5 C modifications has also provided evidence for the epigenetic m 5 C regulation of lncRNA related to HCC tumorigenesis and progression (13). However, the specific genomic distribution of m 5 C-related genes for HCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have performed quantitative mapping of the m5C sites in Arabidopsis thaliana on a transcriptome range, and found more than 1000 m5C sites in mRNA, long non-coding RNA and other non-coding RNAs ( David et al, 2017 ). He et al (2020a) found that compared with adjacent non-tumor tissues, lncRNA m5C methylation occurs more frequently in Hepatocellular Carcinoma(HCC), and more methylated genes are up-regulated. KEGG pathway enrichment analysis show that hypermethylated genes are closely related to cancer pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the modification of lncRNAs could mediate transcription repression [ 54 ]. Third, lncRNA modifications might alter its subcellular distribution [ 185 , 186 ]. Finally, lncRNA modifications regulate the stability of lncRNAs like H19, MALAT1, XIST, etc.…”
Section: Discussionmentioning
confidence: 99%